A possible territorial or recognition behavior of Leptoglossus zonatus (Dallas) (Heteroptera, Coreidae) - Panizzi,Antônio R. (2004)
The coreid Leptoglossus zonatus (Dallas, 1852) is commonly found in corn (Zea mays L.) fields in Brazil, and it has been observed flying and landing on objects or persons near these fields. During January, 1995, this behavior was studied in corn plantations. Results indicated that the bugs concentrated on objects (plastic cylinders traps) introduced into their habitat and that their number increased during the first 24 hs. However, as time passed (8 days), this possible territorial or recognition behavior gradually decreased, and tended to disappear.